Pengaruh Brand Image Dan Brand Awareness Terhadap Keputusan Pembelian - Nel Arianty; Ari Andira (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
The purpose of this study was to determine and analyze the effect of brand image on purchasing decisions, to know and analyze the effect of brand awareness on purchasing decisions, and to find out and analyze the effect of brand image and brand awareness on purchasing decisions of LTD helmet products (Case Study of Faculty of Economics Students And Business, Muhammadiyah University, North Sumatra). The approach used in this research is an associative approach. The population in this study were all students of FEB UMSU and the sample used in this study were 100 people using accidental sampling. Data collection techniques in this study used a questionnaire. Data analysis techniques in this study used Multiple Linear Regression, Classic Assumption Test, t Test and F Test, and the Coefficient of Determination. Data processing in this study uses the SPSS software program (version 24.00). Partially known that brand image has a positive and significant influence on purchasing decisions. Partially, it is known that brand awareness has a positive and significant influence on purchasing decisions. Simultaneously known brand image and brand awareness have a significant influence on purchasing decisions.